Co-creation of social innovations for healthy ageing in rural Europe – a process evaluation of a volunteer-led guided conversation toolkit using Normalisation Process Theory (NPT) - Basharat Hussain; Mahrukh Mirza; Shukru Esmene; Catherine Leyshon; Michael Leyshon; Arunangsu Chatterjee (Journal of Responsible Innovation)
We critically explored the use of Normalisation Process Theory (NPT) in the evaluation of a co-designed intervention toolkit for Healthy Ageing through Innovation in Rural Europe (HAIRE). The toolkit was co-designed and implemented in rural communities in Belgium, France, the Netherlands and the United Kingdom. NPT was applied as a novel analytical framework to shed light on key practices and processes that supported implementation. Further, the paper discusses how social innovation research helps frame co-designing such interventions with local communities. During the study, 25 semi-structured interviews were conducted with project partners and volunteers who were involved in toolkit co-design and implementation. A need for co-designing toolkits that explore ageing holistically was identified. Holistic understandings of ageing can be developed by paying attention to person-centred and place-based (context-specific) aspects of ageing. Finally, we illustrate how NPT can guide future evaluation frameworks as it offers the flexibility required to understand context-specific implementation.